Effects of mineral trioxide aggregate and formocresol on vital pulp after pulpotomy of primary molars: An in vivo study - Brinda Godhi; P B Sood; Arun Sharma (Contemporary Clinical Dentistry, 2011)
Background: Preservation of pulp vitality is of utmost importance to the normal physiological functioning of tooth in situ and physiological process of exfoliation in a tooth affected by disease or trauma. Pulpotomy serves such a purpose using various medicaments applied directly on vital pulp. Aim: The aim of this study was to evaluate clinically and radiographically the effects of mineral trioxide aggregate (MTA) and formocresol (FC) as a pulp dressing after coronal pulp amputation (pulpotomy) in primary molars prospectively over a period of 1 year. Materials and Methods: Thirty-three healthy children, aged between 5 and 8 years, requiring pulp therapy were selected after clinical and radiographic assessment. A total of 50 maxillary and mandibular primary molars were treated by the conventional pulpotomy technique. The teeth were divided into two equal groups. In Group A, FC was used as the pulp dressing agent, and in Group B, MTA was used before restoration with stainless steel crowns. The research employed was a prospective study. The teeth treated were assessed postoperatively after 1, 3, 6 and 12 months. The observations were tabulated and statistically analyzed. Results: Clinically, both the groups showed 100% success at 1, 3, 6 and 12 months. At 3 months, the radiographic success rates of FC and MTA were 92% and 96%, respectively, and at 6 and 12 months, the radiographic success rates of FC and MTA were 88% and 96%, respectively. Conclusion: MTA showed a higher success rate than FC and may be a favorable material for pulpotomy in primary molars whose pulps have been compromised by a carious or mechanical pulp exposure